Patuq dalam Tradisi Kematian Masyarakat Desa Kuta: Sebuah Tinjauan Antropologi Hukum Islam (Patuq in the Tradition of Death of Kuta Villagers: An Anthropological Review of Islamic Law) - Rahman, Fachrir (Samarah: Jurnal Hukum Keluarga dan Hukum Islam, 2019)
Ceremonies are one of the traditional traditions that still have a value that is relevant to the needs of the Society. Religious rituals aim to seek connection with the occult world of natural rulers, this is what encourages people to perform the Ritual. On the other hand, the ritual has become a hereditary inheritance. As well as the tradition of the death ceremony in the village of Kute is a part of religious practice that is historically inspired by certain conditions both religious and local.  Related to it then it can be a drum: how to practice the ritual Patuk and what are the emerging factors and the growing practice of Patuk in Kuta village in the review of the Islamic law anthopology. To answer the question of the problem, the authors use qualitative research by using anthropological approach.